2002
DOI: 10.1074/jbc.m204571200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Laccase from the FungusTrametes versicolor at 1.90-Å Resolution Containing a Full Complement of Coppers

Abstract: Laccase is a polyphenol oxidase, which belongs to the family of blue multicopper oxidases. These enzymes catalyze the one-electron oxidation of four reducing-substrate molecules concomitant with the four-electron reduction of molecular oxygen to water. Laccases oxidize a broad range of substrates, preferably phenolic compounds. In the presence of mediators, fungal laccases exhibit an enlarged substrate range and are then able to oxidize compounds with a redox potential exceeding their own. Until now, only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
640
0
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 815 publications
(679 citation statements)
references
References 41 publications
20
640
0
19
Order By: Relevance
“…The starting geometry of the trinuclear Cu site was adapted from the crystal structure of Trametes versicolor Lc (1GYC, Res. 1.9 Å) (29), in which the His ligands were replaced by imidazolyl ligands. To fully reflect the features of the crystal structure, (i) the positions of the H atoms that replaced the side chains to the protein backbone and those bound to His N not bound to Cu (all involved in hydrogen bonds) were fixed; (ii) the angle of the O atom on the T2 water-derived ligand relative to the plane of the two T2 His rings was fixed to prevent it from artificial binding to the nearby T3 His ligands; and (iii) the three N-Cu T3␣ -Cu T3␤ -N dihedral angles, where N is the coordinated atom of the eclipsed His ligand, were fixed to keep the eclipsed conformation as found in the crystal structures of all MCOs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting geometry of the trinuclear Cu site was adapted from the crystal structure of Trametes versicolor Lc (1GYC, Res. 1.9 Å) (29), in which the His ligands were replaced by imidazolyl ligands. To fully reflect the features of the crystal structure, (i) the positions of the H atoms that replaced the side chains to the protein backbone and those bound to His N not bound to Cu (all involved in hydrogen bonds) were fixed; (ii) the angle of the O atom on the T2 water-derived ligand relative to the plane of the two T2 His rings was fixed to prevent it from artificial binding to the nearby T3 His ligands; and (iii) the three N-Cu T3␣ -Cu T3␤ -N dihedral angles, where N is the coordinated atom of the eclipsed His ligand, were fixed to keep the eclipsed conformation as found in the crystal structures of all MCOs.…”
Section: Methodsmentioning
confidence: 99%
“…A Glu residue near the T3 site appears to play a significant role in stabilizing the structure found in the AO and CotA crystals, because it is well positioned for hydrogen bonding with the azide(s), directly or via water molecules. This Glu (E 510 in AO and E 498 in CotA) is in the putative solvent channel (19,29), and the azide may well have been trapped by this residue in the crystals (prepared by soaking the resting crystals in azide solution). Notably, DFT calculations indicate that the NI Az structure is lower in energy than the T3 -1,1 end-on bridged structure of CotA (SI Fig.…”
mentioning
confidence: 99%
“…pombe (37.1 %). The alignment and the manual examination of the Pc-Fet3 coding sequence revealed that the catalytic histidines participating in the copper centres (Piontek et al, 2002) are encoded in exons II, III, V and VI. In contrast, in Pc-MCO1, these histidines are encoded in exons III, V, VI, VII, XVI, XIX and XX.…”
Section: Identification and Characterization Of Pc-fet3mentioning
confidence: 99%
“…The crystal structure of the Sac. cerevisiae Fet3p and its subsequent superposition with laccase from Trametes versicolor (Piontek et al, 2002) showed several differences in the surroundings of the aromatic-substrate-binding pocket observed in laccases (Taylor et al, 2005). It has been generally stated that Fet3p and ceruloplasmin are the only members of the MCO family that show ferroxidase activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation